Komputerowe wspomaganie zarządzania i procesów decyzyjnych w gospodarce * Metody i algorytmy obliczeniowe w systemach wspomagania decyzji * Komputerowe wspomaganie decyzji wykorzystujące oceny preferencji decydenta - Hryniewicz, Olgierd (1948– ); Nycz, Piotr (Instytut Badań Systemowych. Polska Akademia Nauk, 2002)
In the paper problems of the selection of the most preferred decisions are presented. ft has been assumed that decision maker's preferences are described by flexible constraints. Flexible constraints are modelled by fuzzy sets described by respective membership functions whose values represent preferences assigned to possible solutions. Methods of finding the most preferred solution that have been proposed in the literature are described. One of this method - maxmin method - has been used in the computer program for finding preferred solutions of decision problems. The program is briefly described in the paper.
[5], 135-145 stron ; 21 cm
Bibliografia s. 145